2019
DOI: 10.3389/fpsyg.2019.00226
|View full text |Cite
|
Sign up to set email alerts
|

The Environmental Commons in Urban Communities: The Potential of Place-Based Education

Abstract: The reflections of 205 4–12th graders (most from racial/ethnic minority backgrounds) on what they learned from participating in place-based stewardship education (PBSE) projects in their urban communities were analyzed. All projects involved hands-on collective learning/action by teams of students, teachers, and community partners in the communities where students attended school. Reflections were analyzed using an iterative process of deductive and inductive coding and identifying emergent themes. Deductive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 31 publications
1
31
0
3
Order By: Relevance
“…Many schools and community groups provide programs that engage children in such activities, but few include a research or evaluation component. One exception—though it is not focused on climate change—is work that involves eco‐justice education through place‐based stewardship programs with children and youth, often in poor and marginalized urban contexts (Flanagan, Gallay, Pykett, & Smallwood, ). Through local environmental projects, participants developed greater awareness and appreciation of the natural world and the value of collective action.…”
Section: Supporting Children and Youth In The Developed Worldmentioning
confidence: 99%
“…Many schools and community groups provide programs that engage children in such activities, but few include a research or evaluation component. One exception—though it is not focused on climate change—is work that involves eco‐justice education through place‐based stewardship programs with children and youth, often in poor and marginalized urban contexts (Flanagan, Gallay, Pykett, & Smallwood, ). Through local environmental projects, participants developed greater awareness and appreciation of the natural world and the value of collective action.…”
Section: Supporting Children and Youth In The Developed Worldmentioning
confidence: 99%
“…Pro-environmental activities can be perceived as meaningful and intrinsic experiences with nature [ 8 , 9 ]. For example, Marshall et al [ 10 ] found that pro-environmental behaviors and climate change beliefs were related to a set of altruistic orientations such as understanding, empathy, and concerns for others.…”
Section: Introductionmentioning
confidence: 99%
“…Within the environmental themes, the codes could be broadly classified into two subthemes attitudinal and behavioral changes ( Figure 4 ), which were related to the realization of students on the two elements of the collective importance of the environment ( Flanagan et al, 2019 ), ‘the natural resources on which life depends’ and ‘collective actions to protect a community’s resources.’…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, innovative teaching methods are needed to facilitate students’ learning and experience of concepts of sustainability and to foster a pro-sustainability attitude amongst them ( Ely, 2018 ). In recent years, ever more pedagogies have proved effective in arousing students’ environmental awareness and nurturing their environmentally conscious attitudes, such as problem-based and project-based learning ( Cörvers et al, 2016 ; Leal Filho et al, 2016 ), nature-based and/or outdoor experiential learning ( Lugg, 2007 ; Krasny and Delia, 2015 ), place-based education ( Flanagan et al, 2019 ) and service-based learning ( Zint et al, 2014 ). Other representative pedagogies, such as the jigsaw approach to collaborative learning and mind mapping, were also summarized by Lozano et al (2017) , with corresponding competencies reviewed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation